Investigation of the Performance of Aucore-Pdshell/C as the Anode Catalyst of Direct Borohydride-Hydrogen Peroxide Fuel Cell - Hong Wang; Ying Wang; Xianyou Wang; Peiying He; Lanhua Yi; Wei Yi; Xue Liu (International Journal of Electrochemistry)
The carbon-supported bimetallic Au-Pd catalyst with core-shell structure is prepared by successive reduction method. The core-shell structure, surface morphology, and electrochemical performances of the catalysts are characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), ultraviolet-visible absorption spectrometry, linear sweep voltammetry, and chronopotentiometry. The results show that the Au-Pd/C catalyst with core-shell structure exhibits much higher catalytic activity for the direct oxidation of NaBH4 than pure Au/C catalyst. A direct borohydride-hydrogen peroxide fuel cell, in which the Au-Pd/C with core-shell structure is used as the anode catalyst and the Au/C as the cathode catalyst, shows as high as 68.215 mW cm−2 power density.